Fujita-type theorems for doubly degenerate parabolic equations with a time-weighted source. Issue 5 (3rd May 2016) - Martynenko, A.V.
Abstract : This work deals with the Cauchy problem for a doubly degenerate parabolic equation with a time-weighted source. Existence and non-existence results for global solutions of this problem are established. Sharp estimates of the solution are obtained in the case of global solvability.